Analysis of Translation Techniques on ENFI's (恩菲) Organizational Structure Based on Job Training - Jessy; Siagian, Novita Kristin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research discusses translation techniques in the ENFI’s (恩菲) organizational structure. This research aims to describe the types of translation techniques used in the translation results of ENFI’s (恩菲) organizational structure by Mr. Zhang. In this study the theory used is the theory of translation techniques by Molina & Albir (2002). The research method used in this research is a qualitative descriptive method. The data source in this study is the ENFI’s（恩菲) organizational structure document and its translation. The results showed that the types of translation techniques applied by Mr. Zhang to the ENFI’s（恩菲) organizational structure were modulation, amplification, common equivalents, pure borrowing, reduction, generalization, literal, linguistic compression and discursive creation.